Tansel KORKMAZ, Editör ARCHITECTURE in Turkey Around 2000:ISSUES in DISCOURSE AND PRACTICE (Chamber of Architects of Turkey, Ankara 2005;iv+175 pp) ISBN 975-395890-0 - Korkmaz, Tansel (My University, 2007)
[Abstract Not Available]